Impact of Supervisor’s Support on Job Performance: Mediating Role of Idiosyncratic Deals and Prosocial Motivation - Barik, Pratibha; Uprety, Minal; Mohapatra, Amiya Kumar; G. R., Savitha (Prabandhan: Indian Journal of Management, 2025)
Purpose : The study aimed to explore the mediating role of task and work responsibility idiosyncratic deal (I-deal) and prosocial motivation toward the shared relationship between perceived supervisor’s support and in-role job performance of female academicians in higher education institutions (HEIs). Design/Methodology/Approach : The study was conducted among female academicians of private higher education institutes of Chhattisgarh, with a sample size of 476, comprising 397 female academicians and 79 Dean/Associate Dean/Registrar/HoDs (for prosocial motivation). A structural equation modelling (SEM) method was used to develop and examine the sequential mediation model through SPSS and Hayes PROCESS Model 6. Findings : The results revealed that the perceived supervisor’s support positively and significantly affected the in-role job performance with an effect size of 0.402 under the confidence interval of 95% and a confidence interval with a range of 0.301 to 0.502. It was also revealed that the perceived supervisor’s support positively influenced the task and work responsibility I-deal but negatively influenced prosocial motivation with an effect of 0.827 and –0.159, respectively. The mediation effect of prosocial motivation showed a negative but significant effect on the relationship between the perceived supervisor’s support and in-role job performance with an effect size of –0.117, while task and work responsibility I-deal had an insignificant mediating effect. Additionally, the task and work responsibility I-deal and prosocial motivation did not play a significant sequential mediating effect in the shared perceived supervisor’s support and in-role job performance relationship. Practical Implications : Based upon the outcome of this research, the policymakers and leaders can design a strategic framework for creating collaborative and supportive work environments in HEIs to improve the employee’s in-job performance. In designing the framework, they should consider the role of supervisors to support their employees in terms of work negotiation, particularly when there is a low prosocial motivation. Originality : This research aimed to thoroughly examine the customized work arrangements and prosocial motivation among female faculty members in HEIs. Future research should focus on other geographical areas and different organizational setups to derive an effective strategy for improving the work culture and performance.